Consider the 2nd degree equation ax2 + bx + c = 0. Dividing all terms by , we get:
How , we can write the equation this way.
x2 - Sx + P = 0
Compose the 2nd degree equation whose roots are -2 and 7.
The sum of the roots corresponds to:
S = x1 + x2 = -2 + 7 = 5
The root product corresponds to:
P = x1 . x2 = ( -2) . 7 = -14
The 2nd degree equation is given by x2 - Sx + P = 0, where S = 5 and P = -14.
So x2 - 5x - 14 = 0 is the searched equation.
Form the 2nd degree equation of rational coefficients, knowing that one of the roots is .
If a 2nd degree equation of rational coefficients has a root , the other root will be .
Soon, x2 - 2x - 2 = 0 is the equation sought.